2021
DOI: 10.1007/s00705-021-05152-5
|View full text |Cite
|
Sign up to set email alerts
|

The potential use of microRNAs as a therapeutic strategy for SARS-CoV-2 infection

Abstract: Coronavirus disease 2019 (COVID-19) is caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). To date, there is no effective therapeutic approach for treating SARS-CoV-2 infections. MicroRNAs (miRNAs) have been recognized to target the viral genome directly or indirectly, thereby inhibiting viral replication. Several studies have demonstrated that host miRNAs target different sites in SARS-CoV-2 RNA and constrain the production of essential viral proteins. Furthermore, miRNAs have lower toxici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 195 publications
(228 reference statements)
0
37
0
1
Order By: Relevance
“…The non-natural double-stranded RNA synthesized using this technology is designed to have a 5′ end with a motif that is partially complementary to a specified sequence in the 3′-UTR of the target gene. If this piece of RNA, which mimics an endogenous miRNA, is present in the cell, it can attach specifically to its target gene and cause post-transcriptional inhibition of the target gene [ 178 ].…”
Section: Covid-19 Nucleic Acid-based Therapeuticsmentioning
confidence: 99%
See 2 more Smart Citations
“…The non-natural double-stranded RNA synthesized using this technology is designed to have a 5′ end with a motif that is partially complementary to a specified sequence in the 3′-UTR of the target gene. If this piece of RNA, which mimics an endogenous miRNA, is present in the cell, it can attach specifically to its target gene and cause post-transcriptional inhibition of the target gene [ 178 ].…”
Section: Covid-19 Nucleic Acid-based Therapeuticsmentioning
confidence: 99%
“…Antagomirs (also known as blockmirs) are synthetically designed molecules that are used to antagonize miRNAs oligonucleotides. Antagomirs are entirely complementary to the mature miRNA sequence and contain a variety of phosphonothioate moieties to increase their stability [ 178 ]. Steric blocking mechanism, as well as hybridization to miRNA, allows these anti-miRs to be used as an additional control and for treatment of certain cellular disorders.…”
Section: Covid-19 Nucleic Acid-based Therapeuticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent evidence has indicated that, in general, endogenous human miRNAs (small, single-stranded~22 nt RNAs, such as miRNA-146a) might have a significant antiviral role and hence may be useful to the host in an innate-immune defense by targeting the single-stranded viral ribonucleic acid (ssvRNA) genomes of several different neurotropic viruses, such as SARS-CoV-2, and function to downregulate or modulate their expression [77,78]. To this end, and to quote just one recent example, RNA sequencing and other analytical genetics in RNA-based sequence studies have shown that at least~160 of the~2650 of the 18-22 nt naturally occurring human single-stranded miRNAs have per-fect complementarity within the miRNA-mRNA 'seed region' of the SARS-CoV-2 ssvRNA genome, and these include the unique hsa-miRNA-146a ribonucleotide sequence and those of other related microRNA gene families [47,73,[79][80][81]. Interestingly, the apparent lack of nucleic acids detectable within the prion particle indicates that some yet poorly understood pathological mechanism is responsible for the prion-mediated upregulation of miRNA-146a when neurons are confronted with infection by these neurological-disease inducing sialoglycoproteins [16,53,60,75,82,83].…”
Section: Neurotropic Viral-mediated Induction Of Hsa-mirna-146a-5pmentioning
confidence: 99%
“…Thus, human miRNAs can have a dual role: they can promote the stability and replication of viral RNA, or they can reinforce the host antiviral response. Consequently, miRNAs are considered as promising tools to explore the regulatory networks behind the immune response to COVID-19 infection and to vaccination [ 43 , 44 ].…”
Section: Introductionmentioning
confidence: 99%